Enhancing creative narrative writing skills and multimodal communication competence through a digital storytelling-based project-based learning model - Rasyid, Yulianti; Satria, Dadi; Hayati, Yenni (BAHASTRA, 2025)
A fundamental gap between the demand for multimodal communication competence in the digital era and conventional, text-centric writing pedagogy in higher education was the foundational problem for this research. This study investigated the effectiveness of an integrated learning model, combining Project-Based Learning (PjBL) and Digital Storytelling (DST), as a solution to simultaneously enhance students' creative narrative writing skills and multimodal communication competence. The research employed a quasi-experimental pretest-posttest nonequivalent control group design involving 60 Indonesian Language and Literature Education students, divided into an experimental group (n=30) and a control group (n=30). The results demonstrated a statistically significant advantage for the experimental group, which exhibited substantially greater improvement in creative narrative writing skills (t(58) = 20.45, p < .001) and achieved superior multimodal communication competence scores (t(58) = 16.98, p < .001) compared to the control group. The study concluded that the integration of PjBL and DST is an effective and robust pedagogical intervention for equipping students with holistic literacy skills relevant to the 21st century, successfully bridging traditional writing practices with contemporary digital communication demands.